2001
DOI: 10.1122/1.1333001
|View full text |Cite
|
Sign up to set email alerts
|

Droplet breakup in concentrated emulsions

Abstract: In this paper we report an experimental study on the conditions for droplet breakup in concentrated emulsions under simple shear flow. We present a set of experiments where the ratio between drop and matrix viscosity was varied from 0.1 to 22 and the volume fraction ranged from 0% to 70%. It was observed that the critical shear rate for breakup decreased by more than an order of magnitude for the most concentrated emulsions. Further, drops with viscosity ratio of 22 were seen to rupture in simple shear as soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 9 publications
4
64
0
Order By: Relevance
“…In support of this view, the resemblance of the flow curves in Figure 7 to those in the emulsions showing droplet break up modelled by Jansen et al [35] is striking. …”
Section: Emulsions Inspection Of the T-t G Values Insupporting
confidence: 73%
“…In support of this view, the resemblance of the flow curves in Figure 7 to those in the emulsions showing droplet break up modelled by Jansen et al [35] is striking. …”
Section: Emulsions Inspection Of the T-t G Values Insupporting
confidence: 73%
“…A broad set of data for drops deformation and break up, including a large class of two-dimensional (2D)-flows-covering from simple shear up to a purely elongational flow-was provided by Bentley and Leal [28]. More recently, for emulsions subjected to simple shear flows, Jansen [29] has shown that the critical capillary number decreases with increments of the fraction of the disperse phase: Ca rup (p, φ). Droplet-breaking mechanisms and shapes of Newtonian liquid droplets have been extensively studied.…”
Section: Breakup Of Droplets Under a Shearing Flowmentioning
confidence: 99%
“…For Ca just above CaC the droplet typically breaks into two fragments, while for Ca >> CaC it stretches into a long fluid thread that breaks into many fragments. For non-Newtonian continuous phases (e.g., non-dilute emulsions or continuous phases with thickeners) the continuous phase viscosity is usually replaced by the apparent emulsion viscosity at the prevailing shear rates (e.g., [9,12,17]). …”
Section: Droplet Break-up In 2d Linear Flowsmentioning
confidence: 99%